Large atypical lipomatous tumours of the limbs: A report of three cases - Amrane Hemza; Boussha Toufik; Hasrouri Ilies; Mekideche Besma; Moussa Amrane; Benmayouf Nazim; Derdous Chaouki; Khernane Nacer (Scripta Medica)
Atypical lipomatous tumours (ALT) are rare adipocytic neoplasms classified under well-differentiated liposarcomas. Although they have low metastatic potential, their progressive growth and anatomical location can lead to significant functional impairments. Complete surgical excision remains the primary treatment; however, challenges arise when these tumours are located near critical neurovascular structures. This study presents three clinical cases of large ALT in the limbs, analysing the diagnostic, surgical and prognostic aspects. This study reports on three patients (ages 64, 70 and 69) who presented with large, slowly growing lipomatous masses in the limbs, evolving over several years. The tumours, ranging from 25 to 60 cm in size, were assessed using imaging techniques, including MRI and CT scans. Surgical excision was performed in all cases, ensuring complete tumour resection while preserving adjacent neurovascular structures. Histopathological analysis confirmed the diagnosis of ALT. Postoperative functional recovery and recurrence were monitored over a follow-up period of 24 months. All patients experienced significant clinical improvement, with full restoration of joint mobility and resolution of sensory disturbances. No local tumour recurrence was observed. Postoperative imaging demonstrated effective tissue regeneration without excessive fibrosis or adhesions. The quality-of-life assessment using the Toronto Extremity Salvage Score (TESS) indicated a marked improvement in motor function and autonomy. ALT, despite being a low-grade tumour, requires a multidisciplinary approach for optimal management. Complete surgical excision ensures excellent long-term outcomes, but extended clinical and radiological surveillance remains crucial. Advancements in molecular pathology and imaging techniques may further refine treatment strategies and enhance patient prognosis.